Change Organizations in Planned Change - A Closer Look - Karasvirta Saara; Teerikangas Satu (Taylor & Francis, 2022)
Despite a plethora of frameworks and processes, in planned organizational change models (POCMs), the role of change organizations, i.e. organizations dedicated to change, remains rarely explored. In this paper, we delve into this subject via a multiple case-based research design studying eleven large Finnish companies via 33 interviews. We find that although all studied case companies bear some component(s) of change organizations, these vary substantially. To this end, our findings bear three contributions. First, we propose a typology on change organizations as consisting of change networks, change teams and individual change roles, incorporating varying dimensions each. We further found three interrelations between these dimensions. Second, we demonstrate that change organizations exist in company practice more than they appear in the POCM literature. Third, we develop a framework for the evaluation of the maturity of a company's change organization. Going forward, our findings are a call for further research on change organizations and their role in planned organizational change.MAD statementThis article aims to Make a Difference (MAD) by offering a coherent lens that can be used both in the research and in the development of change organizations, in theory and in practice. Change organizations (networks, teams and roles dedicated to change) are a somewhat underrepresented dimension in classic planned organizational change models. However, in practice, companies' change organizations play various active roles in planned change. Building on evidence from a multiple case study of eleven Finnish large companies, we suggest a multi-dimensional typology on change organizations. Through identified interrelations, we suggest that certain types of change organizations may be preferred over others in particular circumstances. In addition, we offer a change organization maturity framework for developing and evaluating companies' change organizations.